Composite hard carbon material and preparation method thereof, negative active material, negative pole piece and secondary battery

By preparing composite hard carbon materials with porous soft carbon outer layer and closed-porous hard carbon inner layer, the problems of low efficiency and capacity attenuation of existing hard carbon anode materials in sodium ion batteries are solved, and higher battery performance and longer life are achieved.

CN119637847APending Publication Date: 2025-03-18YONGJIANG LAB
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202411814950.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-10
Publication Date
2025-03-18

AI Technical Summary

Technical Problem

The existing hard carbon anode material has low Coulomb efficiency and fast capacity decay in sodium ion batteries, which limits its application in sodium ion batteries.

Method used

A method of preparing composite hard carbon materials is adopted to form a precursor through the hydrothermal reaction of phenolic compounds, ammonia water and aldehyde compounds, and hydrothermal reaction and carbonization with the sugar solution to form a composite structure with porous soft carbon in the outer layer and closed-porous hard carbon in the inner layer.

Benefits of technology

Improves the battery capacity, rate performance and cycle performance, reduces volume expansion and extends battery life.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119637847A_ABST
    Figure CN119637847A_ABST
Patent Text Reader

Abstract

The invention provides a composite hard carbon material and a preparation method thereof, a negative electrode active material, a negative electrode pole piece and a secondary battery, and the preparation method of the composite hard carbon material comprises the following steps: mixing a phenolic compound, ammonia water and an aldehyde compound to obtain a dispersion liquid, and carrying out a first hydrothermal reaction to obtain a precursor; the precursor is mixed with a sugar solution, a second hydrothermal reaction and carbonization treatment are performed to obtain the composite hard carbon material, the composite hard carbon material comprises closed-cell hard carbon and porous soft carbon, and the porous soft carbon is located on at least part of the surface of the closed-cell hard carbon. Therefore, the composite hard carbon material of which the outer layer is porous soft carbon and the inner layer is closed-pore-rich hard carbon is obtained, the gram volume and the conductivity of the composite hard carbon material are improved, the volume expansion of the composite hard carbon material can be reduced by virtue of the porous outer layer and the closed-pore structure of the inner layer, and the capacity, the rate capability and the cycle performance of the battery are further improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of batteries, and in particular, to a composite hard carbon material and a preparation method thereof, a negative electrode active material, a negative electrode plate and a secondary battery. Background Art

[0002] With the rapid development of renewable energy, sodium-ion batteries have attracted much attention as a potential alternative energy storage solution. Compared with traditional lithium-ion batteries, sodium-ion batteries have the advantages of low cost, abundant sodium resources, high reversible capacity and low working potential. However, sodium ions have a relatively large radius and exhibit low sodium storage performance. In this context, hard carbon has attracted widespread attention as a potential negative electrode material for sodium-ion batteries. Hard carbon is considered to be an ideal negative electrode material for sodium-ion batteries because of its abundant resources, low cost and good conductivity. Because hard carbon materials have rich micropores and mesoporous structures, they are conducive to the rapid insertion and extraction of sodium ions, so that the battery can still maintain a high capacity under high-rate conditions. In addition, hard carbon is not prone to volume expansion during the sodium ion insertion and extraction process, so it can effectively inhibit dendrite growth and improve battery safety.

[0003] However, the hard carbon negative electrode materials in the related technology have problems such as low initial coulombic efficiency and fast capacity decay in practical applications, which greatly limits their further application in sodium ion batteries. Therefore, developing hard carbon negative electrode materials with high specific capacity, excellent rate performance and good cycle stability, and optimizing their preparation process are of great significance for promoting the commercial application of sodium ion batteries. Summary of the invention

[0004] The present application aims to solve one of the technical problems in the related art at least to some extent.

[0005] The first aspect of the present application provides a method for preparing a composite hard carbon material, the method comprising mixing a phenolic compound, ammonia water, and an aldehyde compound to obtain a dispersion, obtaining a precursor through a hydrothermal reaction; mixing the precursor with a sugar solution, subjecting the mixture to a hydrothermal reaction and a carbonization treatment, the carbonization treatment comprising a first carbonization treatment and a second carbonization treatment performed sequentially, the temperature of the first carbonization treatment being 500°C-700°C, and the temperature of the second carbonization treatment being 1300°C-2000°C, to obtain the composite hard carbon material, the composite hard carbon material comprising closed-cell hard carbon and porous soft carbon, the porous soft carbon being located on at least a portion of the surface of the closed-cell hard carbon.

[0006] Thus, the present application can obtain a composite hard carbon material with a porous soft carbon outer layer and a closed-cell hard carbon inner layer. The closed-cell hard carbon has a larger pore size, which can accommodate more ions and increase the capacity of the battery. The porous soft carbon has a larger pore size, which helps to increase the diffusion speed and cycle stability of ions, thereby improving the rate performance and cycle performance of the battery. The porous soft carbon can also provide a larger specific surface area, provide abundant embedding sites, and increase the storage capacity of the composite hard carbon material. The porous outer layer and closed-cell inner layer structure can effectively reduce the volume expansion of the composite hard carbon material and extend the battery life.

[0007] According to some embodiments of the present application, the method satisfies at least one of the following conditions: the first carbonization treatment lasts for 1 hour to 3 hours; the second carbonization treatment lasts for 2 hours to 4 hours. Thus, a composite hard carbon material is formed with an outer layer of porous soft carbon and an inner layer of closed-pore-rich hard carbon.

[0008] According to some embodiments of the present application, the ratio of the precursor to the sugar solution is 1:(0.5-5). Thus, the content of the porous structure and the closed-cell structure in the composite hard carbon material is controlled.

[0009] According to some embodiments of the present application, the amount of ammonia added is 1%-10% of the phenolic compound, thereby controlling the degree of cross-linking of the resin to form a resin with suitable hardness, strength and toughness.

[0010] According to some embodiments of the present application, the mass ratio of the phenolic compound to the aldehyde compound is 1:(1-4). Thus, while increasing the curing reaction rate, the uniformity of the performance of the resin after curing is also increased.

[0011] According to some embodiments of the present application, the method satisfies at least one of the following conditions: the phenolic compound includes at least one of phenol, cresol, resorcinol, and tert-butylphenol; the aldehyde compound includes at least one of formaldehyde, acetaldehyde, polyformaldehyde, and furfural.

[0012] According to some embodiments of the present application, the temperature of the hydrothermal reaction is 180° C.-220° C., and the time of the hydrothermal reaction is 5 h-15 h. Thus, while increasing the chemical reaction rate, the phase change of the material and the generation of defects are reduced.

[0013] The second aspect of the present application provides a composite hard carbon material, which is prepared by the method provided by the first aspect of the present application, and the composite hard carbon material satisfies at least one of the following conditions: the pore volume of the composite hard carbon material is 0.08 cm 3 / g-0.15cm 3 / g; the BET specific surface area of ​​the composite hard carbon material is 2.4m 2 / g-5m 2 / g. Therefore, the composite hard carbon material proposed in this application has a porous soft carbon outer layer and a closed-pore hard carbon inner layer. The closed-pore hard carbon has a larger pore size and can accommodate more ions, thereby increasing the capacity of the battery. The porous soft carbon has a larger pore size, which helps to increase the diffusion rate and cycle stability of ions, thereby improving the rate performance and cycle performance of the battery. The porous soft carbon can also provide a larger specific surface area and abundant embedding sites, thereby increasing the storage capacity of the composite hard carbon material. In addition, the porous outer layer and the closed-pore inner layer structure can effectively reduce the volume expansion of the composite hard carbon material and extend the battery life.

[0014] The third aspect of the present application provides a negative electrode active material, including the composite hard carbon material prepared by the method provided in the first aspect of the present application or the composite hard carbon material provided in the second aspect of the present application.

[0015] The fourth aspect of the present application provides a negative electrode plate, comprising the negative electrode active material provided in the third aspect of the present application.

[0016] The fifth aspect of the present application provides a secondary battery, comprising the negative electrode plate provided by the fourth aspect of the present application. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] The above and / or additional aspects and advantages of the present application will become apparent and easily understood from the description of the embodiments in conjunction with the following drawings, in which:

[0018] Figure 1 A schematic flow chart of a method for preparing a composite hard carbon material according to an embodiment of the present application is shown.

[0019] Figure 2 The XRD pattern of the hard carbon provided in Comparative Example 3 of the present application is shown.

[0020] Figure 3 The XRD pattern of the soft carbon provided in Comparative Example 4 of the present application is shown.

[0021] Figure 4 The XRD pattern of the composite hard carbon material of Example 3 of the present application is shown. DETAILED DESCRIPTION

[0022] The embodiments of the present application are described in detail below. The embodiments described below are exemplary and are only used to explain the present application, and should not be construed as limiting the present application. If no specific technology or conditions are indicated in the embodiments, the technology or conditions described in the document in this area or the product specification are used. The reagents used or the instruments that do not indicate the manufacturer are all conventional products that can be obtained commercially.

[0023] The first aspect of the present application provides a method for preparing a composite hard carbon material, the method comprising mixing a phenolic compound, ammonia water, and an aldehyde compound to obtain a dispersion, obtaining a precursor through a hydrothermal reaction; mixing the precursor with a sugar solution, subjecting the mixture to a hydrothermal reaction and a carbonization treatment, the carbonization treatment comprising a first carbonization treatment and a second carbonization treatment performed sequentially, the temperature of the first carbonization treatment being 500°C-700°C, and the temperature of the second carbonization treatment being 1300°C-2000°C, to obtain the composite hard carbon material, the composite hard carbon material comprising closed-cell hard carbon and porous soft carbon, the porous soft carbon being located on at least a portion of the surface of the closed-cell hard carbon.

[0024] Thus, the present application can obtain a composite hard carbon with a porous soft carbon outer layer and a closed-cell hard carbon inner layer. The closed-cell hard carbon has a larger pore size, which can accommodate more ions and increase the capacity of the battery. The porous soft carbon has a larger pore size, which helps to increase the diffusion speed and cycle stability of ions, thereby improving the rate performance and cycle performance of the battery. The porous soft carbon can also provide a larger specific surface area and increase the storage capacity of ions. The porous outer layer and closed-cell inner layer structure can effectively reduce the volume expansion of the composite hard carbon material and extend the battery life.

[0025] The method provided by this application is described in detail below. Figure 1 , the method comprising:

[0026] S10: Mix the phenolic compound, ammonia water, and aldehyde compound to obtain a dispersion, and perform a hydrothermal reaction to obtain a precursor.

[0027] According to some embodiments of the present application, a phenolic compound is dissolved in deionized water, and then ammonia water and an aldehyde compound are added in sequence. The solution can be heated while stirring to obtain a dispersion. The dispersion is transferred to a hydrothermal axe and reacted in a closed hydrothermal kettle. After the reaction is completed, the hydrothermal kettle is cooled to room temperature, the obtained solid particles are washed with deionized water and ethanol, and then the solid particles are placed in an oven for drying to obtain a precursor.

[0028] According to some embodiments of the present application, the phenolic compound includes at least one of phenol, cresol, resorcinol, and tert-butylphenol.

[0029] According to some embodiments of the present application, the aldehyde compound includes at least one of formaldehyde, acetaldehyde, paraformaldehyde, and furfural.

[0030] According to some embodiments of the present application, the temperature of the hydrothermal reaction is 180° C.-220° C., and the time of the hydrothermal reaction can be 5 h-15 h.

[0031] Therefore, by setting the temperature and time of the hydrothermal reaction within the above ranges, the reaction rate is increased.

[0032] As an example, the temperature of the hydrothermal reaction can be 180° C., 190° C., 200° C., 210° C., 220° C., etc., or can be a range consisting of any of the above values.

[0033] As an example, the time of the hydrothermal reaction can be 5 h, 7 h, 9 h, 11 h, 13 h, 15 h, etc., or can be a range consisting of any of the above numerical values.

[0034] According to some embodiments of the present application, the amount of ammonia added is 1%-10% of the mass of the phenolic compound, for example, 1%, 3%, 5%, 7%, 9%, 10%, etc., or can be a range of any of the above values. Thus, the degree of cross-linking reaction of the resin is controlled to obtain a resin with suitable strength, hardness and toughness.

[0035] According to some embodiments of the present application, the mass ratio of the phenolic compound to the aldehyde compound is 1:(1-4), for example, it can be 1:1, 1:2, 1:3, 1:4, etc., or it can be a range of any of the above values. In this way, the degree of the curing reaction is controlled, and while the reaction rate is increased, the uniformity of the cured resin is improved, and the comprehensive performance of the resin is improved.

[0036] S20: Mixing the precursor with the sugar solution, subjecting the mixture to a hydrothermal reaction and a carbonization treatment to obtain the composite hard carbon material

[0037] According to some embodiments of the present application, the precursor is mixed with a sugar solution, transferred to a hydrothermal kettle for a hydrothermal reaction, and after washing and vacuum drying, a first carbonization treatment and a second carbonization treatment are sequentially performed under a protective atmosphere to obtain a composite hard carbon material, wherein the composite hard carbon material includes closed-pore hard carbon and porous soft carbon, and the porous soft carbon is located on at least a portion of the surface of the closed-pore hard carbon.

[0038] According to some embodiments of the present application, the ratio of the precursor to the sugar solution is 1:(0.5-5), for example, it can be 1:0.5, 1:1, 1:2, 1:3, 1:4 or 1:5, etc., or it can be a range composed of any of the above values. Thus, by making the mass ratio of the precursor to the sugar solution within the above range, the number of closed pores in the composite hard carbon material can be adjusted, thereby improving the electrochemical performance of the composite hard carbon material.

[0039] As an example, the sugar solution includes one or both of a glucose solution and a sucrose solution.

[0040] According to some embodiments of the present application, the temperature of the hydrothermal reaction is 180°C-220°C, and the time of the hydrothermal reaction is 5h-15h. Thus, the rate of the chemical reaction is increased, the conversion of the precursor is more complete, the formation of hard carbon is promoted, and the phase change and defect generation are reduced, thereby improving the conductivity of the material.

[0041] As an example, the temperature of the hydrothermal reaction can be 180° C., 190° C., 200° C., 210° C., 220° C., etc., or can be a range consisting of any of the above values.

[0042] As an example, the time of the hydrothermal reaction can be 5 h, 7 h, 9 h, 11 h, 13 h, 15 h, etc., or can be a range consisting of any of the above numerical values.

[0043] It should be noted that the temperature of the hydrothermal reaction during the preparation of the precursor and the hydrothermal reaction after the precursor and the sugar solution are mixed may be the same or different.

[0044] According to some embodiments of the present application, the carbonization treatment includes a first carbonization treatment and a second carbonization treatment performed sequentially.

[0045] According to some embodiments of the present application, the temperature of the first carbonization treatment is 500°C-700°C, and the time is 1h-3h. For example, the temperature of the first carbonization treatment can be 500°C, 550°C, 600°C, 650°C, 700°C, etc., or can be a range composed of any of the above values; the time of the first carbonization treatment can be 1h, 1.5h, 2h, 2.5h, 3h, etc., or can be a range composed of any of the above values.

[0046] Therefore, by keeping the temperature and time of the first carbonization treatment within the above range, the residual precursor can be reduced and the purity of the material can be improved. At the same time, the structure of the material can be prevented from undergoing transitional transformation to form amorphous carbon or graphitization, which would affect the electrochemical properties of the composite hard carbon material.

[0047] According to some embodiments of the present application, the temperature of the second carbonization treatment is 1300°C-2000°C, and the time is 2h-4h. For example, the temperature of the second carbonization treatment can be 1300°C, 1500°C, 1700°C, 1900°C, 2000°C, etc., or can be a range composed of any of the above values; the time of the second carbonization treatment can be 2h, 3h, 4h, etc., or can be a range composed of any of the above values.

[0048] Therefore, by setting the temperature and time of the second carbonization treatment within the above ranges, the carbonization can be carried out more thoroughly, thereby increasing the hardness and toughness of the composite hard carbon material and improving its stability.

[0049] The second aspect of the present application provides a composite hard carbon material, which is prepared by the method provided by the first aspect of the present application. The composite hard carbon material includes closed-cell hard carbon and porous soft carbon, and the porous soft carbon is located on at least a portion of the surface of the closed-cell hard carbon.

[0050] Therefore, the composite hard carbon material provided by the present application has a porous soft carbon outer layer and a closed-cell hard carbon inner layer. The closed-cell hard carbon has a larger pore size, which can accommodate more ions and increase the capacity of the battery. The porous soft carbon has a larger pore size, which helps to increase the diffusion speed and cycle stability of ions, thereby improving the rate performance and cycle performance of the battery. The porous soft carbon can also provide a larger specific surface area and increase the storage capacity of ions. The porous outer layer and closed-cell inner layer structure can effectively reduce the volume expansion of the composite hard carbon material and extend the battery life.

[0051] According to some embodiments of the present application, the pore volume of the composite hard carbon material is 0.08 cm 3 / g-0.15cm 3 / g. For example, it can be 0.08cm 3 / g, 0.1cm 3 / g, 0.12cm 3 / g, 0.14cm 3 / g, 0.15cm 3 / g, etc., or can be within the range of any of the above values. Thus, the migration rate of ions is increased, and the rate performance of the battery is improved.

[0052] In the present application, the pore volume of the composite hard carbon material can be measured by a nitrogen adsorption-desorption method (BET method).

[0053] According to some embodiments of the present application, the BET specific surface area of ​​the composite hard carbon material is 2.4 m 2 / g-5m 2 / g. For example, it can be 2.4m 2 / g, 2.8m 2 / g, 3.2m 2 / g, 3.6m 2 / g, 4m 2 / g, 4.4m 2 / g, 4.8m 2 / g, 5m 2 / g, etc., or can be any range of the above values. Therefore, the composite hard carbon material has a large specific surface area, which can provide abundant embedding sites for active ions during battery cycling, thereby increasing the storage capacity of the composite hard carbon material.

[0054] In the present application, the test method of the BET specific surface area of ​​the composite hard carbon material is: place the sample cell in an environment of liquid nitrogen temperature (generally -196°C) and gradually inject nitrogen. Record the amount of nitrogen adsorption under different pressures, usually using the isotherm method. After the adsorption is completed, gradually reduce the pressure of the nitrogen and record the amount of nitrogen released during the desorption process. According to the BET theory, the specific surface area is calculated using the data of the adsorption isotherm, and the adsorption data is fitted by the BET equation to obtain the specific surface area.

[0055] The third aspect of the present application provides a negative electrode active material, including the composite hard carbon material prepared by the method provided in the first aspect of the present application or the composite hard carbon material provided in the second aspect of the present application.

[0056] The fourth aspect of the present application provides a negative electrode plate, comprising the negative electrode active material provided in the third aspect of the present application.

[0057] The fifth aspect of the present application provides a secondary battery, comprising the negative electrode plate provided by the fourth aspect of the present application.

[0058] As an example, the secondary battery may be a lithium ion battery or a sodium ion battery.

[0059] The embodiments of the present application are described in detail below. The embodiments described below are exemplary and are only used to explain the present application, and should not be construed as limiting the present application. If no specific technology or conditions are indicated in the embodiments, the technology or conditions described in the document in this area or the product specification are used. The reagents used or the instruments that do not indicate the manufacturer are all conventional products that can be obtained commercially.

[0060] Example 1

[0061] (1) Preparation of precursor: 3 g of phenol was dissolved in 30 mL of deionized water, and then 1.6 mL of ammonia water (mass concentration of 25%-28%) and 6 mL of paraformaldehyde were added in sequence. The dispersion was obtained after magnetic stirring at 40°C for 12 h. The dispersion was transferred to a hydrothermal kettle for hydrothermal reaction at a temperature of 180°C for 5 h. After the reaction, the hydrothermal kettle was cooled to room temperature. The obtained solid particles were washed three times with deionized water and ethanol respectively, and dried in an oven at 80°C to obtain a precursor.

[0062] (2) Preparation of dispersion: 4 g of glucose was weighed and dissolved in 30 mL of deionized water, and then magnetically stirred for 4 h to obtain a glucose solution.

[0063] (3) Preparation of composite hard carbon material: The precursor obtained in step (1) was dissolved in the dispersion obtained in step (2), and after magnetic stirring for 4 h, it was transferred into a hydrothermal reactor and hydrothermalized at 180 °C for 14 h. After the reaction was completed, the hydrothermal reactor was cooled to room temperature. The obtained solid particles were washed with deionized water and ethanol three times each, dried in an oven at 80 °C, and then heated at 700 °C for 14 h. 2 The first carbonization treatment was carried out in N atmosphere for 1 h, and after cooling to room temperature, the carbonization was carried out in N atmosphere at 1700 °C. 2 A hard carbon composite material was obtained after a second carbonization treatment in atmosphere for 1 h.

[0064] Example 2

[0065] (1) Preparation of precursor: 5 g of cresol was dissolved in 30 mL of deionized water, and then 1.9 mL of ammonia water (mass concentration of 25%-28%) and 8 mL of acetaldehyde were added in sequence. After magnetic stirring at 40°C for 12 h, a dispersion was obtained. The dispersion was transferred to a hydrothermal kettle for hydrothermal reaction at a temperature of 180°C for 5 h. After the reaction, the hydrothermal kettle was cooled to room temperature. The obtained solid particles were washed three times with deionized water and ethanol respectively, and dried in an oven at 80°C to obtain a precursor.

[0066] (2) Preparation of dispersion: 4 g of glucose was weighed and dissolved in 30 mL of deionized water, and then magnetically stirred for 4 h to obtain a dispersion.

[0067] (3) Preparation of composite hard carbon material: The precursor obtained in step (1) was dissolved in the dispersion obtained in step (2), and after magnetic stirring for 4 h, it was transferred into a hydrothermal reactor and hydrothermalized at 180°C for 14 h. After the reaction was completed, the hydrothermal reactor was cooled to room temperature. The obtained solid particles were washed with deionized water and ethanol three times each, dried in an oven at 80°C, and then heated at 500°C for 14 h. 2 The first carbonization treatment was carried out in N atmosphere for 2 h, and then cooled to room temperature and heated at 1600 °C. 2 After a second carbonization treatment in atmosphere for 2 hours, a composite hard carbon material was obtained.

[0068] Example 3

[0069] (1) Preparation of precursor: 2 g of resorcinol was dissolved in 30 mL of deionized water, and then 1.5 mL of ammonia water (mass concentration of 25%-28%) and 3.7 mL of formaldehyde were added in sequence. The dispersion was obtained after magnetic stirring at 40°C for 12 h. The dispersion was transferred to a hydrothermal kettle for hydrothermal reaction at a temperature of 200°C for 6 h. After the reaction, the hydrothermal kettle was cooled to room temperature. The obtained solid particles were washed three times with deionized water and ethanol respectively, and dried in an oven at 80°C to obtain a precursor.

[0070] (2) Preparation of dispersion: 6 g of glucose was weighed and dissolved in 30 mL of deionized water, and then magnetically stirred for 4 h to obtain a dispersion.

[0071] (3) Preparation of composite hard carbon material: The precursor obtained in step (1) was dissolved in the dispersion obtained in step (2), and after magnetic stirring for 4 h, it was transferred into a hydrothermal reactor and hydrothermalized at 200 °C for 10 h. After the reaction was completed, the hydrothermal reactor was cooled to room temperature. The obtained solid particles were washed with deionized water and ethanol three times each, dried in an oven at 80 °C, and then heated at 600 °C for 10 h. 2 The first carbonization treatment was carried out in N atmosphere for 2 h, and then cooled to room temperature and heated to 1400 °C. 2 After the second carbonization treatment in the atmosphere for 2 hours, the composite hard carbon material was obtained. The XRD test diagram of the composite hard carbon material is Figure 4 , it can be seen that the composite hard carbon material includes both hard carbon and soft carbon.

[0072] Example 4

[0073] (1) Preparation of precursor: 2.5 g of tert-butylphenol was dissolved in 30 mL of deionized water, and then 1.8 mL of ammonia water (mass concentration of 25%-28%) and 4.5 mL of furfural were added in sequence, and a dispersion was obtained after magnetic stirring at 40°C for 12 h. The dispersion was transferred to a hydrothermal kettle for hydrothermal reaction, and then the hydrothermal kettle was sealed and hydrothermalized at 220°C for 4 h. After the reaction, the hydrothermal kettle was cooled to room temperature, and the obtained solid particles were washed with deionized water and ethanol three times each, and placed in an oven at 80°C for drying to obtain a precursor.

[0074] (2) Preparation of dispersion: Weigh 4 g of glucose and dissolve it in 30 mL of deionized water, then stir it magnetically for 4 h to obtain a base dispersion.

[0075] (3) Preparation of composite hard carbon material: The precursor obtained in step (1) was dissolved in the dispersion obtained in step (2), and after magnetic stirring for 4 h, it was transferred into a hydrothermal reactor and hydrothermalized at 220 °C for 10 h. After the reaction was completed, the hydrothermal reactor was cooled to room temperature. The obtained solid particles were washed with deionized water and ethanol three times each, dried in an oven at 80 °C, and then heated at 500 °C for 10 h. 2 The first carbonization treatment was carried out in N atmosphere for 2 h, and then cooled to room temperature and heated to 1700 °C. 2 After a second carbonization treatment in atmosphere for 1 hour, a composite hard carbon material was obtained.

[0076] Comparative Example 1

[0077] (1) Preparation of dispersion: 2 g of resorcinol was dissolved in 30 mL of deionized water, and 1.5 mL of aqueous ammonia (mass concentration of 25%-28%) and 3.7 mL of formaldehyde were added in sequence. The dispersion was obtained after magnetic stirring at 40° C. for 12 h.

[0078] (2) Preparation of glucose solution: Weigh 4 g of glucose and dissolve it in 30 mL of deionized water, then stir it magnetically for 4 h to obtain a Glu-based dispersion.

[0079] (3) Preparation of glucose (Glu)-based precursor: The glucose solution in step (2) was transferred into a hydrothermal reactor, which was then sealed and hydrothermalized at 200°C for 6 h. After the reaction was completed, the hydrothermal reactor was cooled to room temperature, and the obtained solid particles were washed with deionized water and ethanol three times each, and dried in an oven at 80°C to obtain a glucose-based precursor.

[0080] (4) Preparation of composite hard carbon material: The glucose precursor obtained in step (3) was dissolved in the dispersion of step (1), and after magnetic stirring for 4 h, it was transferred into a hydrothermal reactor and hydrothermalized at 200 °C for 10 h. After the reaction, the hydrothermal reactor was cooled to room temperature. The obtained solid particles were washed with deionized water and ethanol three times each, dried in an oven at 80 °C, and then heated at 600 °C for 10 h. 2 The first carbonization was carried out in N atmosphere for 2 h, and then cooled to room temperature and heated at 1400 °C. 2 After the second carbonization in the atmosphere for 2 hours, a composite hard carbon material with an inner layer of porous soft carbon and an outer layer of closed-pore-rich hard carbon was obtained.

[0081] Comparative Example 2

[0082] (1) Preparation of glucose solution: Weigh 4 g of glucose and dissolve it in 30 mL of deionized water. Then, stir the mixture under magnetic stirring for 4 h to obtain a glucose solution.

[0083] (2) Preparation of dispersion: Weigh 2 g of resorcinol and dissolve it in 30 mL of deionized water. Then add 1.5 mL of ammonia water (mass concentration is 25%-28%) and 3.7 mL of formaldehyde in sequence. After magnetic stirring at 40° C. for 12 h, a dispersion is obtained.

[0084] (3) Preparation of precursor: The glucose solution in step (1) and the dispersion in step (2) were transferred into a hydrothermal reactor, and then the hydrothermal reactor was sealed and hydrothermaled at 200° C. for 6 h. After the reaction was completed, the hydrothermal reactor was cooled to room temperature, and the obtained solid particles were washed with deionized water and ethanol three times each, and placed in an oven at 80° C. for drying.

[0085] (4) Preparation of composite hard carbon material: The material obtained in step (3) was washed with deionized water and ethanol three times each, dried in an oven at 80°C, and then heated at 600°C for 1 hr at 400°C. 2 The first carbonization was carried out in N atmosphere for 2 h, and then cooled to room temperature and heated at 1400 °C. 2 After the second carbonization in atmosphere for 2 hours, a composite hard carbon material was obtained.

[0086] Comparative Example 3

[0087] (1) Preparation of dispersion: 2 g of resorcinol was dissolved in 30 mL of deionized water, and 1.5 mL of aqueous ammonia (mass concentration of 25%-28%) and 3.7 mL of formaldehyde were added in sequence. The dispersion was obtained after magnetic stirring at 40° C. for 12 h.

[0088] (2) Preparation of precursor: The dispersion in step (1) was transferred into a hydrothermal reactor, which was then sealed and hydrothermalized at 200°C for 6 h. After the reaction was completed, the hydrothermal reactor was cooled to room temperature. The obtained solid particles were washed with deionized water and ethanol three times each, and dried in an oven at 80°C.

[0089] (3) Preparation of hard carbon material: The material obtained in step (2) was washed with deionized water and ethanol three times each, dried in an oven at 80°C, and then heated at 600°C for 1 hr at 400°C. 2 The first carbonization was carried out in N atmosphere for 2 h, and then cooled to room temperature and heated at 1400 °C. 2 After the second carbonization in the atmosphere for 2h, a hard carbon material was obtained. The XRD pattern of the hard carbon material is shown in Figure 2 .

[0090] Comparative Example 4

[0091] The soft carbon was purchased from Sichuan Kenye Technology Development Co., Ltd. as pre-calcined oil-based needle coke HEQ1. The XRD pattern of the soft carbon material is shown in Table 3.

[0092] In Examples 1 to 4 and Comparative Examples 1 to 4, the composite hard carbon material is formed on the negative electrode sheet, and the battery is assembled. The method for assembling the battery includes:

[0093] 1. Preparation of positive electrode sheet

[0094] Cut the metallic sodium and nickel foam into small discs for later use.

[0095] 2. Preparation of negative electrode sheet

[0096] The composite hard carbon material, the conductive agent and the binder are mixed in a ratio of 8:1:1, the solvent is added, the mixture is fully ground and then coated on the copper foil, and the mixture is placed in an oven for drying. After drying, the mixture is cut into small pieces and placed in a glove box for later use.

[0097] 3. Preparation of Electrolyte

[0098] The electrolyte was purchased from Vico 014. The electrolyte includes a solvent including dimethyl carbonate (DMC) and ethylene carbonate (EC) in a volume ratio of 1:1, and the electrolyte salt is NaCiO 4 , concentration is 1mol / L.

[0099] 4. Isolation film

[0100] Cut the purchased isolation film into small pieces and put them in the glove box for later use.

[0101] 5. Assemble the battery

[0102] Assemble the half-cell in the glove box in the order of positive electrode shell, negative electrode, electrolyte, separator, electrolyte, positive electrode, negative electrode shell, and then press.

[0103] Performance Testing

[0104] 1. Pore volume of composite hard carbon materials

[0105] The testing process involves placing the sample in cryogenic nitrogen and recording the adsorption and desorption isotherms to analyze the pore volume.

[0106] 2. BET specific surface area of ​​composite hard carbon materials

[0107] Place the sample cell in an environment with liquid nitrogen temperature (generally -196°C) and gradually inject nitrogen. Record the amount of nitrogen adsorption at different pressures, usually using the isotherm method. After the adsorption is completed, gradually reduce the pressure of nitrogen and record the amount of nitrogen released during the desorption process. According to the BET theory, the specific surface area is calculated using the data of the adsorption isotherm, and the specific surface area is obtained by fitting the adsorption data through the BET equation.

[0108] 3. The first coulombic efficiency of the battery

[0109] The battery test was carried out on the Xinwei software, with the test temperature at 30°C, the current at 0.2C, the voltage window at 2V~4V, and constant current charging and discharging.

[0110] 4. Battery discharge capacity

[0111] The battery test was carried out on the Xinwei software, with the test temperature at 30°C, the current at 0.2C, the voltage window at 2V~4V, and constant current charging and discharging.

[0112] 5. Battery charge capacity

[0113] The battery test was carried out on the Xinwei software, with the test temperature at 30°C, the current at 0.2C, the voltage window at 2V~4V, and constant current charging and discharging.

[0114] The test results of the composite hard carbon materials and batteries assembled therefrom in Examples 1 to 4 and Comparative Examples 1 to 4 are shown in Table 1.

[0115] Table 1

[0116]

[0117] Conclusion: By comparing Examples 1-4 with Comparative Examples 1-4, it can be seen that the composite hard carbon material prepared in the present application has a larger pore volume and BET specific surface area. By using the composite hard carbon material provided in the present application as the negative electrode active material of the battery, a battery with a higher first coulombic efficiency, a higher discharge specific capacity and a higher charge specific capacity can be obtained.

[0118] Although the embodiments of the present application have been shown and described above, it can be understood that the above embodiments are exemplary and cannot be understood as limitations on the present application. Ordinary technicians in this field can change, modify, replace and modify the above embodiments within the scope of the present application.

Claims

1. A method for preparing a composite hard carbon material, characterized in that: include: A phenolic compound, ammonia water and an aldehyde compound are mixed to obtain a dispersion, and a precursor is obtained by hydrothermal reaction; The precursor is mixed with a sugar solution, and subjected to a hydrothermal reaction and a carbonization treatment, wherein the carbonization treatment includes a first carbonization treatment and a second carbonization treatment performed sequentially, wherein the temperature of the first carbonization treatment is 500°C-700°C, and the temperature of the second carbonization treatment is 1300°C-2000°C, so as to obtain the composite hard carbon material, wherein the composite hard carbon material includes closed-cell hard carbon and porous soft carbon, and the porous soft carbon is located on at least a portion of the surface of the closed-cell hard carbon.

2. The method according to claim 1, characterized in that The method satisfies at least one of the following conditions: The time of the first carbonization treatment is 1h-3h; The time of the second carbonization treatment is 2h-4h.

3. The method according to claim 2, characterized in that The mass ratio of the precursor to the sugar solution is 1:(0.5-5).

4. The method according to any one of claims 1 to 3, characterized in that The amount of ammonia water added is 1%-10% of the mass of the phenolic compound.

5. The method according to any one of claims 1 to 3, characterized in that: The mass ratio of the phenolic compound to the aldehyde compound is 1:(1-4).

6. The method according to any one of claims 1 to 3, characterized in that Satisfy at least one of the following conditions: The phenolic compound includes at least one of phenol, cresol, resorcinol and tert-butylphenol; The aldehyde compound includes at least one of formaldehyde, acetaldehyde, paraformaldehyde and furfural.

7. The method according to any one of claims 1 to 3, characterized in that The temperature of the hydrothermal reaction is 180° C.-220° C., and the time of the hydrothermal reaction is 5 h-15 h.

8. A composite hard carbon material, characterized in that: The composite hard carbon material is prepared by the method according to any one of claims 1 to 7, and the composite hard carbon material satisfies at least one of the following conditions: The pore volume of the composite hard carbon material is 0.08 cm 3 / g-0.15cm 3 / g; The BET specific surface area of ​​the composite hard carbon material is 2.4 m 2 / g-5m 2 / g.

9. A negative electrode active material, characterized in that: The composite hard carbon material comprises the composite hard carbon material prepared by the method according to any one of claims 1 to 7 or the composite hard carbon material according to claim 8.

10. A negative electrode plate, characterized in that: The negative electrode active material according to claim 9 is included.

11. A secondary battery, characterized in that: Including the negative electrode sheet as described in claim 10.

Citation Information

Patent Citations

  • Soft and hard carbon composite negative electrode material, preparation method thereof and capacitor comprising negative electrode material

    CN107993853A

  • Phenolic resin / sucrose-based hard carbon microsphere material, preparation method thereof and sodium ion battery

    CN112125295A

  • Hard carbon microspheres as well as preparation method and application thereof

    CN114044508A

  • Hard carbon negative electrode material and preparation method thereof, negative electrode plate and sodium ion battery

    CN115557486A

  • Hard carbon material with high initial efficiency and high magnification as well as preparation method and application of hard carbon material

    CN116425139A